2021
DOI: 10.3390/sym13091705
|View full text |Cite
|
Sign up to set email alerts
|

Plant Leaves Recognition Based on a Hierarchical One-Class Learning Scheme with Convolutional Auto-Encoder and Siamese Neural Network

Abstract: In this paper, we propose a novel method for plant leaves recognition by incorporating an unsupervised convolutional auto-encoder (CAE) and Siamese neural network in a unified framework by considering Siamese as an alternative to the conventional loss of CAE. Rather than the conventional exploitation of CAE and Siamese, in our case we have proposed to extend CAE for a novel supervised scenario by considering it as one-class learning classifier. For each class, CAE is trained to reconstruct its positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In this experiment, HC employed the aggregate clustering approach. Hamrouni et al (2021) proposed a plant leaf recognition method based on a hierarchical classification scheme, wherein the test image was first assigned to the nearest cluster and then matched to one class from the classes that fall under the determined cluster using a novel one-class learning classifier. The experimental results demonstrated the superiority of this method.…”
Section: Hierarchical Clusteringmentioning
confidence: 99%
“…In this experiment, HC employed the aggregate clustering approach. Hamrouni et al (2021) proposed a plant leaf recognition method based on a hierarchical classification scheme, wherein the test image was first assigned to the nearest cluster and then matched to one class from the classes that fall under the determined cluster using a novel one-class learning classifier. The experimental results demonstrated the superiority of this method.…”
Section: Hierarchical Clusteringmentioning
confidence: 99%
“…Siamese CNN is a special type of convolutional neural network that is mainly used to process data that require pair comparison, such as determining whether two inputs are similar. Hamrouni et al [32] proposed to use Siamese training to distinguish the similarity and dissimilarity of the obtained samples. The study by Huang et al [33] suggested that the dual-path Siamese CNN could effectively leverage deep cellular neural networks even with limited training samples.…”
Section: Similarity Learningmentioning
confidence: 99%
“…Due to their excellent performance, pre-trained CNNs have been widely used in several computer vision tasks [31,32]. In the literature, there are various pre-trained architectures of CNN which have been trained on large-scale image databases.…”
Section: A Supervised Convolutional Neural Network Architecturementioning
confidence: 99%